Knowledge, attitude, and patient advice on sustainable diets among Spanish health professionals - Fresán, Ujué; Vidal-Carou, M. Carmen; Ramos-Truchero, Guadalupe; Pipaon, Miguel Sáenz de; Moreno, Luis A.; Salas-Salvadó, Jordi (Frontiers in Nutrition, 2023)
Current dietary patterns, especially in high-income countries, are unsustainable. Health professionals, due to their credibility and close contact with the general population, could serve as agents of change for the adoption of sustainable diets. The objective of this study was to assess the knowledge and attitude regarding sustainable diets among the health professionals in Spain. A 24-item online questionnaire was designed for this purpose, and sent to health professionals (i.e., dietitians-nutritionists, nurses, physicians, and pharmacists). From September 2021 to May 2022, 2545 health professionals answered the survey completely. One fifth of them had never heard about the term “sustainable diet”, and most of them recognized having a limited knowledge about it. They considered important promoting sustainable diets when making dietary recommendations, and pointed out that they would like to be trained on the topic. Indeed, they reported that all health professionals, independently of their career background, should be educated on sustainable diets. Efforts should be stressed on implementing training courses, at university level but also as a continuous post-graduate training, providing to health professionals in Spain the necessary knowledge to promote the adoption of sustainable diets among the population.